ADAPTING THE AUDIT PROFESSION TO THE 'NEW NORMAL' IN POST-COVID PERIOD - A CASE STUDY OF THE REPUBLIC OF NORTH MACEDONIA - Trpeska, Marina; Bozhinovska Lazarevska, Zorica; Atanasovski, Atanasko; Dionisijev, Ivan; Malchev, Bojan; Tocev, Todor (Faculty of Economics-Skopje, Ss. Cyril and Methodius University in Skopje, 2023)
Throughout history, disease outbreaks have greatly impacted societies and workplaces, leading to the need for adaptability in various jobs. The accounting and auditing sector, which is crucial for giving reliable information during crises, has faced its own set of challenges during these difficult times. This study looks into how the Covid-19 pandemic affected auditors in the Republic of North Macedonia as they adjusted to the "new normal." We examine how they adapted to working remotely, created virtual strategies, overcame obstacles, and how all this affected their mental health. Our research shows that auditors went through major changes in their work roles during the pandemic. They showed resilience and flexibility, although their experiences varied. They faced increased expectations from stakeholders, changes in their client lists, and had to learn new skills. Despite these challenges, auditors managed to succeed, showing their ability to adapt to change. The experiences of auditors during the pandemic demonstrate their ability to handle disruptions and find new opportunities. These findings are important for those in the auditing field, organizations, and those who make decisions about policies, as they provide insights into how the auditing world is changing in the "new normal." However, this study has some limitations, mainly because it is based on what auditors said about their own experiences, it only looks at one point in time, there might be a bias in who was chosen for the study, and there are limits to the survey used. Future research could look at how auditors' experiences change over time, compare different regions, consider what clients think, study the impact of new technology, look at changes in rules, and compare how auditors are doing with other professionals facing similar issues.
Acknowledgment: We gratefully acknowledge the financial support provided for this research through a scientific research project by the Ss. Cyril and Methodius University in Skopje. This assistance was granted in full compliance with the Regulations for the utilization of funds from the integrative functions of the University for scientific research projects. We extend our sincere appreciation to the University for its invaluable contribution, which played a pivotal role in the successful completion of this research endeavor
Keywords: Post-covid; Auditors; Mental health; North Macedonia